SINTESIS GLUTAMIDA DARI METIL ESTER MINYAK BIJI KARET (Hevea brasiliensis) DENGAN ASAM GLUTAMAT - Citra Uli Sitompul; Chairul Saleh; Daniel Daniel (PROSIDING SEMINAR KIMIA, 2017)
Synthesis of glutamide from methyl ester of rubber seed oil (Hevea brasiliensis) with glutamic acid by amidation reaction has been performed. The synthesis process involves extracting, esterification and amidation. The results showed that rubber seed oil content was 39,75%, acid number 20,98 mg KOH / gr and FFA level was 10,472%. Rubber seed oil was previously converted to methyl esters through esterification process so as to obtain a decrease of FFA to 1.34%. The result of GC-MS analysis shows the most dominant methyl ester composition is methyl linoleate which is 43,11%. The amidation process is carried out by reacting the rubber seed oil methyl esters with glutamic acid. Fourier Transform-Infra Red spectrum of glutamide, showing the absorption peak for N-H group at wave number 3429,43 cm-1 and the absorption peak for C=O amide group at wave number 1643,35 cm-1. Keywords: Rubber Seed Oil, Esterification, Amidation, Glutamide.